Reframing Beauty and Gender in Stage Makeup (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
This chapter by Charlene Gross re-evaluates traditional stage makeup education, advocating for a more effective pedagogy that values diversity. It addresses how the field presumes binary gender and promotes specific beauty standards. Gross proposes a non-judgmental approach using anatomical terminology, decoupling techniques from gender, and incorporating diverse examples. The text explores challenges, especially in remote learning, highlighting the shift to video demonstrations for accessibility and broader student perspectives. Key projects like "Corrective Face," "Slim/Stout," and "Gender Reversal" (now "Drag Transformation") are discussed as evolving to foster a deeper understanding of character, beauty, and gender in performance
Keywords: stage makeup; diversity pedagogy; gender representation; remote learning; performance characterization